Paternity matters: premarital childbearing and belonging in Nyanga East and Mokhotlong. (3rd May 2016) - Mkhwanazi, Nolwazi; Block, Ellen
Abstract : In this article we discuss the role that fathers and paternal families play in acknowledging and caring for children born outside of a recognised union in two southern African communities – Nyanga East, South Africa and Mokhotlong, Lesotho. While these communities are geographically and culturally close, there are important differences in the responses to the care of children born outside of a recognised union. In Nyanga East, despite not paying damages, the genitor and the paternal family are increasingly becoming involved in the care of children, even when they are no longer in a relationship with the mother; whereas in Mokhotlong, if a pregnant woman is not in a formal or informal union with the father, she and her family effectively erase the genitor's role in the child's life. We argue that these local variances in the kinship dynamics arise from people privileging different kinship relationships. We suggest that in both contexts kinship is manipulated in order to find a place where a child will be well cared for, enable educational opportunities for young mothers, and privilege employment opportunities for adults who bring much-needed income into households. The article reinforces the importance of contextually specific understandings of kin relations and a fluid and processual understanding of kinship itself.